English language literacy in rural community setting : an analysis of the environment to encourage and sustain the development of english language learning outside the classroom - Abdul Majid, Norazman; Puteh, Fatimah; Muhammad, Faruk (Faculty of Management and Human Resource Development, 2005)

(untitled)
This study was carried out in an attempt to identify the encouragement and support provided by parents in the learning of the English language at home, identify whether conducive environments are available at home, and to analyze the sustainability of learning of English in the rural area. A questionnaire was prepared and distributed to five different FELDA areas in the Johor Selatan FELDA district. Interview and observation were also carried out to ascertain the conduciveness of the home environment towards the sustenance of the use of English at home. A total number of 78 respondents completed and returned the questionnaires, while a total of 5 interviews were conducted with the settlers. The findings revealed that parents could do many things to sustain the use of English at home. The nature of the work and the level of education made it difficult for them to help their children with the English language. Most of them have a rather positive attitude towards the language. Many of them are aware of the importance of English to their childrens future undertakings and success. Most of them are rather optimistic about their childrens English status. Many of them are changing their attitudes and are making various efforts to help their children excel in education and the English Language. Recommendations for the parents include having workshops organise by FELDA management to teach what the parents can do to help at home, FELDA organise a weekly event to incite interest in the language among students at the individual areas, and work collaboratively to have English programs at the community level, such as having a public library, etc.